Borders, Boundaries and Belonging in Post-Ottoman Space in the Interwar Period
1 online resource
Keywords: Focusing on new nation states and mandates in post-Ottoman territories, Borders, Boundaries and Belonging in Post-Ottoman Space in the Interwar Period examines how people negotiated, imagined or ignored new state borders and how they conceived of or constructed belonging. Through investigations of border crossing, population transfer, exile and emigration, this book explores the intricacies of survival within and beyond newly imposed state borders, the exploitation of opportunities and the human cost of political partition. Contributors are Toufoul Abou-Hodeib, Leyla Amzi-Erdogdular, Amit Bein, Ebru Boyar, Onur İşçi, Liat Kozma, Brian McLaren, Nikola Minov, Eli Osheroff, Ramazan Hakkı Öztan, Michael Provence, Jordi Tejel and Peter Wien.